2021
DOI: 10.3390/pharmaceutics13071048
|View full text |Cite
|
Sign up to set email alerts
|

Sustained In Vitro and In Vivo Delivery of Metformin from Plant Pollen-Derived Composite Microcapsules

Abstract: We developed a dual microencapsulation platform for the type 2 diabetes drug metformin (MTF), which is aimed to increase its bioavailability. We report the use of Lycopodium clavatum sporopollenin (LCS), derived from their natural spores, and raw Phoenix dactylifera L. (date palm) pollens (DPP) for MTF microencapsulation. MTF was loaded into LCS and DPP via a vacuum and a novel method of hydration-induced swelling. The loading capacity (LC) and encapsulation efficiency (EE) percentages for MTF-loaded LCS and M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 134 publications
(208 reference statements)
0
17
0
Order By: Relevance
“…12 The sporopollenin exine shells can serve as an excellent substrate for several types of microcarriers due to their inherent size uniformity, 4,8,13 porosity, 14,15 elasticity, [16][17][18] amphiphilicity, 19 chemical stability, [20][21][22] anti-ultraviolet and anti-oxidation, [23][24][25] photothermal effects, 26 adhesion, [27][28][29] biocompatibility, 30 and stability within body fluids. 31 For example, their inside cavity and surface pores facilitate drug loading and cargo delivery; [30][31][32][33][34] the robust exine structure can achieve long-term preservation; 25 the unique surface decoration increases the specific surface area enhancing the adsorption of probe molecules and target detection; 35 sporopollenin is rich in carboxyl and hydroxyl groups, which can be easily functionalized or formed into composites and further derived into microrobots, 8,36 cell scaffolds, 37,38 etc. Compared to artificial microcarriers, which are complex, expensive and poorly monodispersed in mass production, the intrinsic superiorities and tailorable properties of spores and pollens make them suitable template-free materials to construct biological microcarriers or synthetic biomimetic particles.…”
Section: Introductionmentioning
confidence: 99%
“…12 The sporopollenin exine shells can serve as an excellent substrate for several types of microcarriers due to their inherent size uniformity, 4,8,13 porosity, 14,15 elasticity, [16][17][18] amphiphilicity, 19 chemical stability, [20][21][22] anti-ultraviolet and anti-oxidation, [23][24][25] photothermal effects, 26 adhesion, [27][28][29] biocompatibility, 30 and stability within body fluids. 31 For example, their inside cavity and surface pores facilitate drug loading and cargo delivery; [30][31][32][33][34] the robust exine structure can achieve long-term preservation; 25 the unique surface decoration increases the specific surface area enhancing the adsorption of probe molecules and target detection; 35 sporopollenin is rich in carboxyl and hydroxyl groups, which can be easily functionalized or formed into composites and further derived into microrobots, 8,36 cell scaffolds, 37,38 etc. Compared to artificial microcarriers, which are complex, expensive and poorly monodispersed in mass production, the intrinsic superiorities and tailorable properties of spores and pollens make them suitable template-free materials to construct biological microcarriers or synthetic biomimetic particles.…”
Section: Introductionmentioning
confidence: 99%
“…Due to their robustness, sporopollenin microcapsules (SPMs) have been proposed for various applications, including drug delivery [ 8 , 14 , 15 ]. SPMs with different sizes and morphology can be obtained from a variety of plants, but even though many recent studies have demonstrated the capability of SPMs to control and enhance the delivery of drugs [ 16 , 17 , 18 ], only a few of them concern cutaneous and cosmetical applications [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…(Zhang et al,2019). A case of serious hepatotoxicity is possibly caused by metformin use at a dose of 500 mg/day for three weeks (Nathan,2008;Meligi et al, 2021). In diabetic rats treated with metformin, the pancreas showed that islets of Langerhans have a more-or less-normal cell population with the absence of degenerative changes, and blood sinusoids also appeared to be normal (Meligi et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…A case of serious hepatotoxicity is possibly caused by metformin use at a dose of 500 mg/day for three weeks (Nathan,2008;Meligi et al, 2021). In diabetic rats treated with metformin, the pancreas showed that islets of Langerhans have a more-or less-normal cell population with the absence of degenerative changes, and blood sinusoids also appeared to be normal (Meligi et al, 2021). Drug nanoencapsulation arises to be an effective alternative to lessen the side effects of drug administration while achieving controlled release and site-specific delivery (Kumar et al, 2016).…”
Section: Introductionmentioning
confidence: 99%